Comparative transcriptome and defense hormone analyses of resistant and susceptible tea plant varieties revealed the response mechanisms of tea plants to Apolygus lucorum feeding - Yuan-Hong Wan; Chun Yang; Da-He Qiao; Yue-Xin Li; Xiao-Zeng Mi; Xing-Yun Shi; Shuai Li; Jin-Feng Zhang; Yu-He Wan; Ze-Hong Meng (Plant Stress)
Apolygus lucorum represents a major insect pest affecting Camellia sinensis, with its feeding activity posing significant threats to tea plant growth and yield productivity. However, the molecular basis of tea plant resistance against A. lucorum infestation remains poorly characterized. In this study, we employed two distinct tea varieties, the resistant variety Taixuan 0310 (TX0310) and the susceptible variety Huangjinya (HJY), for comparative analysis. Phenotypic evaluation revealed consistently less severe damage symptoms in TX0310 compared to HJY under identical infestation conditions. Through transcriptome sequencing approaches and integrated phytohormone profiling, we systematically elucidated the differential defense responses to A. lucorum. The resistant variety TX0310 exhibited sustained and comprehensive activation of both jasmonic acid (JA) signaling cascades and secondary metabolic pathways, whereas the susceptible variety HJY displayed only transient and attenuated JA responses. Notably, key genes involved in JA biosynthesis (CsOPR11 and CsJMT) showed marked upregulation specifically in TX0310. Quantitative analysis confirmed significantly higher accumulation of defense-related phytohormones including JA and salicylic acid (SA) in TX0310 relative to HJY. Through weighted gene co-expression network analysis (WGCNA) and Pearson correlation analysis, we identified 10 core regulatory genes (including CsOPR11, CsAOS, and CsJMT). Notably, overexpression of the CsOPR11 gene in tobacco resulted in significantly higher methyl jasmonate (MeJA) levels in CsOPR11-transgenic plants compared to wild-type controls. This provides novel insights into the molecular mechanisms underlying tea plant resistance against insect pests.